Reds [videorecording (DVD)] - Beatty, Warren, 1937-; Beatty, Warren, 1937-; Keaton, Diane; Herrmann, Edward, 1943-2014; Kosinski, Jerzy, 1933-1991; Nicholson, Jack; Sorvino, Paul; Stapleton, Maureen (Paramount, 2006)
The true story of the love affair of John Reed, American Communist, journalist and activist and Louise Bryant, writer and feminist.